Market Integration as a Mechanism of Growth - Wolfgang Keller; Carol H. Shiue (Center for Economic Studies and ifo Institute (CESifo), 2016)
In what sense are institutions a deep determinant of growth? In this paper, we address this question by examining the relationship between city growth and institutional reform in 19th century Germany, when some cities experienced deep institutional reform as a result of French rule. Employing an instrumental-variables approach, we find there is a hierarchy of growth factors in which institutions affect market integration more than market integration affects institutions. It was institutional improvements that were crucial to market integration, rather than just declining transport costs, which increased city growth during this time period. The institutional reforms, however, were transmitted through the mechanism of market integration. This created a much larger impact on city growth compared to the institutional impact independent from the market integration mechanism. The approach we take can be applied to other causes of economic growth.
Keywords: 330; institutions; city size; trade; arbitrage